Language games and blurry terminology: Can clarity enhance athlete development? - Johnston, Kathryn; McAuley, Alexander B. T.; Kelly, Adam L.; Baker, Joseph (Frontiers in Sports and Active Living, 2023)
This perspective focuses on the need for researchers and practitioners to carefully consider the clarity and consistency of their language in the context of athlete development. Evidence supporting a lack of congruency in the way certain terms and expressions are defined, understood, and operationalized continues to accumulate, highlighting the importance of this area for sport stakeholders and the potential looming crises. In systems that regularly rely on precision and accuracy, it will be critical that all involved in the co-creation of knowledge generation and application carefully consider terms that may further complicate athlete development practices. We highlight some potentially blurry terms and draw attention to potential avenues for future research.